Fibre optic angle rate gyroscope performance evaluation in terms of Allan variance. (30th March 2020) - Hu, Jian-Bo; Liu, Bing-Qi; Qiu, Kai
Based on the analysis of the error-sources of the fibre optic angle rate gyroscope (FOARG), the Allan parameters are focused on calculation the Allan variances. The relationship between the Allan variance and the accuracy of FOARG is given. For the existences in the output of some-type FOARG, such as high noise, large volatilities in value and existing notable errors, a data-process algorithm is proposed with meaning and smoothing one. A lot of MATLAB blocks, such as data-sampling, meaning and smoothing, are designed to process some-type FOARG's dynamic data and static data and to evaluate its performance with Allan variance.